Evaluasi Peran Dan Kontribusi Organisasi HMJ PBA UIN Raden Intan Lampung Dalam Meningkatkan Kemampuan Bahasa Arab Mahasiswa - Abdullah Sungkar (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2022)
This article discusses the role and contribution of the student association of Arabic language education department (HMJ PBA) UIN Raden Intan Lampung on Arabic language proficiency in students. The focus of this research is on the realm of program evaluation that has been made by HMJ PBA UIN Raden Intan Lampung. To find out what programs have been programmed by HMJ PBA to assist in improving students' Arabic language skills in the Arabic language education department at UIN Raden Intan Lampung. This research is descriptive qualitative. The results of this study indicate that; 1). The work programs made by HMJ PBA are varied, some are aligned with supporting the objectives of learning Arabic language skills for students, then some are not including language skills but help students in developing soft skills, interests and talents. 2). For the role and contribution given by HMJ PBA UIN Raden Intan Lampung in helping to improve students' Arabic language skills, it still needs to be improved, as the students have high hopes for HMJ PBA as a forum that is able to help students' Arabic proficiency الملخص يناقش هذا البحث دور ومساهمة رابطة طلاب قسم تعليم اللغة العربية بجامعة الإسلامية الحكومية رادين إنتان لامبونج في إتقان اللغة العربية لدى الطلاب. ينصب تركيز هذا البحث على مجال تقييم البرنامج الذي تم إجراؤه بواسطة رابطة طلاب قسم تعليم اللغة العربية بجامعة الإسلامية الحكومية رادين إنتان لامبونج. لمعرفة البرامج التي تمت برمجتها بواسطة رابطة طلاب قسم تعليم اللغة العربية للمساعدة في تحسين مهارات اللغة العربية للطلاب في قسم تعليم اللغة العربية في بجامعة الإسلامية الحكومية رادين إنتان لامبونج. هذا البحث وصفي نوعي. تشير نتائج هذا البحث إلى: 1). تتنوع برامج العمل التي أعدتها رابطة طلاب قسم تعليم اللغة العربية، بعضها يتوافق مع دعم أهداف تعلم مهارات اللغة العربية للطلاب ، ثم لا يشمل بعضها المهارات اللغوية ولكن يساعد الطلاب في تطوير المهارات الشخصية والاهتمامات والمواهب. 2). بالنسبة للدور والمساهمة التي قدمها رابطة طلاب قسم تعليم اللغة العربية بجامعة الإسلامية الحكومية رادين إنتان لامبونج في المساعدة على تحسين مهارات اللغة العربية لدى الطلاب، لا تزال هناك حاجة إلى تحسين، حيث يعلق الطلاب آمالًا كبيرة على رابطة طلاب قسم تعليم اللغة العربية كمنتدى قادر على مساعدة الطلاب باللغة العربية الكفاءة